Aquatic Iguana: A Floating Waste Collecting Robot with IoT Based Water Monitoring System - Mirza Turesinin; Abdullah Md Humayun Kabir; Tanzina Mollah; Sadvan Sarwar; Shazzad Hosain (IAES Indonesia Section, 2020)
Water pollution is a major problem worldwide. In order to tackle the pollution and keeping the water resources clean, this paper presents an affordable and advanced floating garbage removing robot called